Von Malachit zu Kupfer - Nutz, Rainer (Zeitschrift für ägyptische Sprache und Altertumskunde, 2017)
Petrie describes in „Researches in Sinai“ an expedition into Serabit el-Khadim to extract minerals. Newer excavations in Ayn Soukhna allow insight into the reduction of malachite to copper. Reducing malachite to copper proves to be a very energy-intensive process. To obtain the necessary temperatures over a sufficiently long period of time a surprisingly high amount of charcoal has to be mixed with small-grained mineral under constant air supply. In dry climate wood grows comparatively slowly which translates into requirements of larger wooded areas to provide enough wood for the production of charcoal. This research paper aims at collecting pertinent data to improve the transparency of these processes. But only additional parameters will allow better models and help to paint a clearer picture.